The role of dentists on medically compromised children’s oral and dental prophylaxis in Hospital - Roosje Rosita Oewen (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: One of dentist’s main roles is to coordinate the management of medically compromised children. The term of medically compromised refers to those children who have medical conditions which affect the dental treatment or manifest as a specific oral and dental problem. Patient’s visit to Special Care for Dentistry Clinic Dr. Hasan Sadikin Hospital Bandung showed a remarkable increase. From under 10 new visit in 2003, now July–December 2008 showed 81 new visit. Purpose: This paper discusses several medical problems (cardiovascular, hematology, respiratory system, and genetic disorder) in children and the role of dentist in the treatment of those patients in the hospital. Review: The increase of attention by all level to these medically compromised children in the hospital also increases the dentist’s role in supporting the prognosis of the disease and patient’s quality of life. The most important effort is oral and dental prophylaxis to prevent oral pathology which is caused by the manifestation of disease as well as the side effects of treatment. Conclusion: It is, concluded that role of the dentist in managing these patients is giving preventive efforts and dental treatment that may be improve patient’s quality of life. The preventive effort and dental treatment is customize according to the patients condition. Nevertheless, cooperation from the dentist and other professional is needed in treating these patients.